The task and place of missiology at the public university - P. Verster (Acta Theologica)
Although Missiology has been an accepted discipline for over 100 years since Warneck’s important contribution, the teaching of this theological discipline, especially at public universities, is currently under great strain. The question is whether it is at all appropriate to teach Missiology using public funds and propagating only the Christian religion. This paper suggests the following: (a) Missiology is the essence of the church and should be taught as the ministry of reconciliation; (b) Missiology is a discipline that received universal recognition; (c) It remains important to teach theological students the essence of missions as an essential part of theology; (d)Missiology is such an integral part of theological teaching that theology in its entirety is under the same strain if Missiology is rejected. Therefore, it is not the discipline that should receive attention and possibly be adapted, but the way in which it is taught.